The Effect of Modifying Mendoan Tempeh Recipe into Tempeh Perkedel on the Acceptability of Non-Diet Patients in the Inpatient Room of Lotim Medical Center Hospital - Fania Ayu Lestari; AASP Chandradewi; I Gde Narda Widiada; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2024)
Background: Acceptability indicates the success of food preparation, which can be seen in food waste. Food is said to be leftover if the remaining food is >20%. The recipe modification is hoped to reduce the patient's food waste to ≤ 20%.Research Methods: This research is quasi-experimental, using a one-group pretest-posttest design. Sampling in this study used a saturated sampling technique, with a sample size of 24 people in the group before modification and 27 people in the group after modification. Data were analyzed using the Independent T-test.Research Result: Modifying the tempeh mendoan recipe to make tempeh patties significantly influences the average remaining tempeh before and after modification, thus affecting patient acceptance.Conclusion: Modifying the tempe mendoan recipe into tempe patties can reduce the patient's food waste and increase receptivity to the tempe menu.